Post-transplant hypocomplementemia: A novel marker of cardiovascular risk in kidney transplant recipients?. (February 2018) - Maestro de la Calle, Guillermo; Fernández-Ruiz, Mario; López-Medrano, Francisco; Polanco, Natalia; González, Esther; San Juan, Rafael; Ruiz-Merlo, Tamara; Origüen, Julia; Paz-Artal, Estela; Andrés, Amado; Aguado, José María
Abstract: Background and aims: Cardiovascular disease (CVD) is a leading cause of mortality after kidney transplantation (KT). The potential role of the complement system in the pathogenesis of post-transplant CVD remains unexplored. Methods: Serum complement (C3 and C4) levels were measured at baseline and post-transplant months 1 and 6 in 447 kT recipients. The study outcome was post-transplant atherothrombotic event (PAE), a composite of acute coronary syndrome, critical peripheral arterial disease, stroke and/or transient ischemic attack. Results: After a median follow-up of 4.2 years, 48 PAEs occurred in 43 patients (cumulative incidence: 9.6%; incidence rate: 2.6 events per 100 transplant-years). No differences were found in C3 and C4 levels at baseline or month 1 between patients with or without PAE. However, C3 levels at month 6 were significantly lower in patients developing PAE beyond that point (i.e., late PAE) (96.9 ± 22.3 vs. 109.6 ± 24.0 mg/dL; p = 0.013). The presence of C3 hypocomplementemia at month 6 was associated with a lower PAE-free survival ( p = 0.002). After adjusting for conventional CVD risk factors and acute graft rejection, C3 hypocomplementemia at month 6 remained as an independent risk factor for late PAE in all the exploratory models (minimum hazard ratio: 3.24; p = 0.011). With respect to a model exclusively based on clinical variables, the inclusion of C3 levels at month 6 improved predictive capacity (areas under ROC curves: 0.788 and 0.812, respectively). Conclusions: Post-transplant monitoring of serum C3 levels might be useful to identify KT recipients at increased risk of CVD. Highlights: The measurement of serum levels of complement factor C3 constitutes a routine practice in most clinical immunology laboratories. C3 hypocomplementemia at month 6 after kidney transplantation was associated with a three-fold increase in the risk of atherothrombotic events. This association was independent of other well-established risk factors for cardiovascular disease. The inclusion of this parameter improves the accuracy of clinical predictive models for post-transplant cardiovascular disease.